Analisis Hukum Terhadap Penerapan Kebijakan Anti-Dumping di Indonesia dalam Perspektif World Trade Organization (WTO) - Adfari, Tsabitah Rahmah (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
International trade is a vital element for global economic growth, but on the other hand, it opens up opportunities for unfair trade practices such as dumping that can harm domestic industries. To address this, the World Trade Organization (WTO) established the Anti-Dumping Agreement (ADA) as a guideline for implementing anti-dumping policies among member countries. This agreement regulates the basic principles, investigation procedures, and mechanisms for imposing anti-dumping duties to maintain healthy competition and fairness between countries. Indonesia, as a WTO member, has ratified these provisions through Law Number 7 of 1994 and implemented them in various national regulations such as Law Number 7 of 2014 concerning Trade, Government Regulation Number 34 of 2011, and Minister of Trade Regulation Number 75 of 2022, which regulates the role of the Indonesian Anti-Dumping Committee (KADI). Although Indonesia has a clear legal basis and implementation mechanism, the effectiveness of anti-dumping policies still faces challenges such as limited resources, the complexity of the investigation process, and the increasing practice of circumvention dumping. Therefore, it is necessary to strengthen institutional capacity, procedural transparency, and cross-sector coordination so that anti-dumping policies in Indonesia can be implemented effectively, fairly, and in line with the principles of international trade within the WTO framework.